Research on the configuration of commercial facilities around universities based on the characteristics and satisfaction of university students’ consumption behavior - Yang Zhou; Yixuan Zeng; Caiyun Qian (Journal of Asian Architecture and Building Engineering)
University students’ consumption behavior is an important way for them to interact with urban communities effectively. It not only contributes to enhancing the economic, social, and cultural vitality of cities but also plays a role in nurturing growth through environmental factors, promoting the organic integration and sustainable development of campuses and cities. This paper investigates the university students from 15 universities in Nanjing. By leveraging Point of Interest data and field research, it collects data on the functional layout and built environment indicators of commercial facilities surrounding the campuses and analyzes the consumption behavior characteristics of students. Subsequently, correlation analysis and fuzzy-set qualitative comparative analysis are employed, with the commercial facilities and built environment indicators surrounding universities as conditional variables, and the satisfaction scores for four types of commercial facilities as outcome variables. The study explores the core indicators affecting consumption satisfaction and the combination paths of multiple indicators. The results indicate that various types of consumption are influenced by distinct factors and paths. The research conclusions provide reference indicators and a basis for the planning, layout, spatial configuration, and management of commercial facilities surrounding campuses to enhance the multi-dimensional integration and overall sustainable development of universities and cities.